Impact of Patient Resilience on Outcomes of Open Brostrom-Gould Lateral Ligament Repair. (18th November 2021) - Andrews, Nicholas A.; Dib, Aseel; Torrez, Timothy W.; Harrelson, Whitt M.; Sinha, Tanvee; Rallapalle, Vyshnavi; Agarwal, Abhinav; Shah, Ashish
Abstract : Introduction: Little is known about the factors affecting the intermediate outcomes of the Brostrom-Gould repair as measured by new patient-reported outcome instruments and the impact of patient resilience on postoperative outcomes. This is the first study to investigate the impact of resilience on the outcomes of lateral ligament repair. Methods: Retrospectively, 173 patients undergoing Brostrom-Gould at single institution from January 2013 to June 2020 were identified. Patient characteristics, participation in athletic activities, surgical variables, and complications were recorded. Patient-Reported Outcome Measurement Information System (PROMIS) Pain Interference v1.1 (PI), Physical Function v1.2 (PF), and the Foot Ankle Ability Measure (FAAM) were collected. The Brief Resilience Scale was used to quantify resilience. A linear regression model was constructed to evaluate the independent effect of resilience on each PROMIS and FAAM outcome instrument. Variables were included in the regression model based on an a priori significance threshold of P <0.05 in bivariate analysis. Results: Resilience's independent effect on outcome measures was as follows: PROMIS PF (unstandardized β 8.2, 95% confidence interval [CI] 3.9 to 12.6), PROMIS PI (unstandardized β −4.8, 95% CI −7.9 to −1.7), FAAM Activities of Daily Living (unstandardized β 16.6, 95% CI 8.7 to 24.6), and FAAM Sports (unstandardized β 28.4, 95% CI 15.9 to 40.9). Preoperative participation in athletic activities also had a positive independent effect on multiple outcome metrics including PROMIS PF (unstandardized β 9.4, 95% CI 2.8 to 16.0), PROMIS PI (unstandardized β −5.3, 95% CI −10.0 to −0.582), and FAAM Sport scores (unstandardized β 34.4, 95% CI 15.4 to 53.4). Conclusions: Resilience and patient participation in athletic activities are independent predictors of improved postoperative functional outcomes as measured by PROMIS and FAAM instruments at intermediate term follow-up. Resilient patients and athletes reported markedly higher PF and less pain burden postoperatively. Preoperative quantification of resilience could enable improved prognostication of patients undergoing lateral ligament repair of the ankle.